"Heart and Soul of a Prosecutor": The Impact of Prosecutor Role Orientation on Charging Decisions. (February 2022) - Lowrey-Kinberg, Belén; Gould, Jon; Bowman, Rachel
In most research, prosecutors are depicted monolithically as "interchangeable parts" rather than as individuals with varied perspectives. Yet, the prosecution is becoming increasingly diverse, a shift that is likely accompanied by different approaches to prosecution. Drawing upon the concepts of role orientation and job crafting, we identify three primary orientations to the job of a prosecutor, that of the Enforcer, the Reformer, and the Advocate. Whereas Enforcers view their job as merely to apply the law, Reformers focus on rehabilitation of the defendant, and Advocates are instead concerned with retribution for victims. These three interpretations of prosecutors' responsibilities translate into different approaches to charging. Furthermore, when there is a disconnect between a prosecutor's personal philosophy and that of their office more generally, prosecutors develop covert ways of exercising their priorities.